Pengembangan Media Pembelajaran Berbasis Android Materi Tari Anak: Wiraga, Wirama, Wirasa, Dan Pola Lantai Pada Program Studi Pendidikan Guru Anak Usia Dini - Setyowati, Hery; Wulandari, Monica Niken; Sahrul, Sahrul; Muryani, Arlis; Syafi’, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
This study aims to develop Android-based learning media for Children's Dance material, which includes wiraga, wirama, wirasa, and floor patterns in the PGPAUD Study Program. The application is designed as an interactive mobile-based media with YouTube video integration as the main source of material, and has a simple, attractive, and user-friendly display. The method used is research and development (R&D) through the stages of needs analysis, design, development, and evaluation. Data were collected through assessment questionnaires from 60 respondents. The validity test using Pearson's correlation showed that all items were valid with values above the r table (0.312), while the reliability test obtained a Cronbach's alpha value of 0.842, indicating high internal consistency. The effectiveness test results through normalized gain (N-gain) showed a value of more than 0.72 in the high category, which indicates a significant increase in student learning outcomes between the pretest and posttest. These findings indicate that the assessment instrument is suitable for use and that the Android-based learning media developed is effective as an alternative to support Children's Dance learning in PGPAUD because it is able to present material concisely, guide practice, and facilitate systematic understanding of dance elements.